Upregulation of transient receptor potential melastatin 6 channel expression by rosiglitazone and all‐trans‐retinoic acid in erlotinib‐treated renal tubular epithelial cells. Issue 6 (21st November 2018) - Manabe, Aya; Furukawa, Chisa; Hasegawa, Hajime; Matsunaga, Toshiyuki; Endo, Satoshi; Ikari, Akira
Abstract: Anti‐epidermal growth factor receptor (EGFR) drugs including erlotinib cause a side effect of hypomagnesemia. In lung adenocarcinoma A549 cells, anticancer agents such as cisplatin and doxorubicin dose‐dependently increased toxicity, but the effects were significantly suppressed by culturing the cells in low Mg 2+ ‐containing media. To obtain the maximum effect in cancer chemotherapy, it should be necessary to prevent the reduction of body Mg 2+ content. Anti‐EGFR drugs inhibit EGF‐induced elevation of transient receptor potential melastatin 6 (TRPM6) Mg 2+ channel in renal tubular epithelial NRK‐52E cells. Here, we found that rosiglitazone, an antidiabetic drug, and all‐ trans ‐retinoic acid (ATRA), a vitamin A derivative, increase the messenger RNA (mRNA) level of TRPM6 in the presence of erlotinib. The rosiglitazone‐ and ATRA‐induced elevation of mRNA level, Mg 2+ influx, and promoter activity of TRPM6 were inhibited by GW‐9662, a potent antagonist of peroxisome proliferator‐activated receptor (PPAR)γ, and LE135, a retinoic acid receptor (RAR) antagonist, respectively. Rosiglitazone increased the phosphorylation and nuclear localization levels of PPARγ, which were inhibited by GW‐9662. In contrast, RAR was mainly distributed in the nuclei under control conditions, which was unchanged by ATRA and LE135. The promoter activity of TRPM6 was inhibited by a mutation in the peroxisome proliferator hormone response element (PPRE). A chromatin immunoprecipitation assay revealed that PPARγ and RAR bind to the PPRE, which was blocked by GW‐9662 and LE135, respectively. These results suggest that rosiglitazone and ATRA reverse the reduction in Mg 2+ reabsorption caused by anti‐EGFR drugs. Abstract : Rosiglitazone and all‐ trans ‐retinoic acid (ATRA) increased transient receptor potential melastatin 6 (TRPM6) expression in renal tubular epithelial cells. Rosiglitazone and ATRA increased Mg 2+ influx. Rosiglitazone and ATRA may reverse the reduction in Mg 2+ reabsorption caused by antiepidermal growth factor receptor (anti‐EGFR) drugs.